A Model for Assessing the Causality of Factors in the Development of Voluntary Pension Insurance in the Republic of Kazakhstan - Dmitry Nazarov; Aliya Bayakhmetova; Lyazzat Bayakhmetova; Leila Bayakhmetova (Mathematics, 2022)
Many countries have been experiencing a crisis in their pension systems for fiscal and demographic reasons. Voluntary pension funds are a way out of the crisis. The depth of the problem lies in the study of social and economic-mathematical aspects in making economic decisions on implementing voluntary contributions. The authors studied sustainable development, considering the assessment of the causal relationship between factors in the development of voluntary pension insurance in the Republic of Kazakhstan. The article analyzes pension system models and studies the experience of the OECD countries. The results of the analysis highlight the most important factors affecting the development of pension systems with an emphasis on voluntary pension insurance mechanisms. The authors propose a conservative, economic, extended economic, and extended intermediate solution for building a set of cause-and-effect models for the development of voluntary pension insurance in the Republic of Kazakhstan based on a survey of a representative sample of citizens in the Republic of Kazakhstan using the QCA method.